Participatory Action Research as an Approach for Sustainable Post-Graduate Supervision in Higher Education - Molise, Habasisa; Kola, Malose (Journal of Posthumanism, 2026)
The generation of knowledge is a defining attribute of universities, yet many South African institutions face challenges in achieving this effectively, particularly in postgraduate supervision. This study explores participatory action research (PAR) as a catalyst for sustainable postgraduate supervision in higher education. Using a qualitative approach and systematic literature review (SLR) of 12 studies, the research identified five key themes: fostering participation and collaborative support, nurturing cordial student–supervisor relationships, promoting democratic and emancipatory supervision, enhancing communication and constructive feedback, and applying a cohort supervision model. The findings suggest that PAR can shift supervision from hierarchical, individualistic models toward interactive, empowering practices that enhance postgraduate success. By addressing power dynamics and emphasizing collaborative engagement, supervision becomes more sustainable. The study recommends adopting a co-supervision model, where responsibilities are shared among supervisors, enabling students to benefit from diverse expertise while reducing the workload on individual supervisors.